1981
DOI: 10.1007/bf01541435
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of the male schizophrenic: The impact of illness and medications

Abstract: The literature concerning the impact of (a) the schizophrenic illness and (b) the neuroleptic drugs (which are the most commonly employed medications for this disorder) on male sexual behavior is critically reviewed in the light of what is currently known about the interaction of both the schizophrenic illness and the neuroleptic drugs with hormones and neurotransmitters known to play a role in male sexual behavior. The effect of the schizophrenic illness on male sexual behavior is unclear, but there are some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 75 publications
0
20
0
2
Order By: Relevance
“…A study of depressed male outpatients found that the most consistent nding was diminished sexual satisfaction (as opposed to diminished sexual activity or interest) (Nofzinger et al, 1993). Similarly, although schizophrenia is generally characterized by diminished sexual interest and activity, few systematic studies have been published documenting this assumption (Nestoros et al, 1991;Friedman & Harrison, 1984). It was reported that 49% of people with schizophrenia, 36.2% of those with an affective disorder and 13.3% of control patients (dermatology outpatients) had a sexual dysfunction.…”
Section: Sexual Dysfunction and Psychiatric Illnessmentioning
confidence: 97%
“…A study of depressed male outpatients found that the most consistent nding was diminished sexual satisfaction (as opposed to diminished sexual activity or interest) (Nofzinger et al, 1993). Similarly, although schizophrenia is generally characterized by diminished sexual interest and activity, few systematic studies have been published documenting this assumption (Nestoros et al, 1991;Friedman & Harrison, 1984). It was reported that 49% of people with schizophrenia, 36.2% of those with an affective disorder and 13.3% of control patients (dermatology outpatients) had a sexual dysfunction.…”
Section: Sexual Dysfunction and Psychiatric Illnessmentioning
confidence: 97%
“…14,30 Many factors can influence sexual functioning in patients with schizophrenia, like the primary illness, antipsychotic treatment, comorbid somatic disorders, relationship factors, the degree of social competence, previous (positive or negative) sexual experiences, or social consequences such as (self)stigmatization and discrimination. [1][2][3][4]93 When patients attribute sexual dysfunction only to medication, this may increase the risk of nonadherence to medication. This underlines the importance to consider with patients which factors are important in their individual situation, in case of a relationship preferably together with their partner.…”
Section: Psychosocial Treatment Strategies and General Considerationsmentioning
confidence: 99%
“…Rarely is sex conceptualized as "an act of communication, expression of emotion, or an attempt at interpersonal bonding" (Lilleleht & Leiblum, 1993, p. 252). Rather, many clinicians believe that their clients are asexual, that their sexuality is inappropriate, or that they are incapable of successful romantic relationships (Buckley et al, 1999;Hogan, 1980;Lilleleht & Leiblum;Nesteros, Lehman, & Ban, 1981;Sadow & Corman, 1983;Thomas, 1989;Vandereycken, 1993). In short, sexual behavior is seen as another symptom to be treated or as a possible risk factor for slowing or reversing recovery (Pinderhughes, Barrabee, & Reyna, 1972).…”
Section: Indiana University-purdue University Indianapolismentioning
confidence: 96%